Meningkatkan Kesejahteraan Perekonomian Masyarakat Melalui Kelompok Usaha Bersama (KUBE) Di Desa Batuyang Kecamatan Pringgabaya Kabupaten Lombok Timur - Immy Suci Rohyani; Mulyana Hidayani; Ratnah Hartinah (Universitas Mataram, 2020)
West Nusa Tenggara is one of the provinces in Indonesia in which the poverty rate is still high. This condition requires the government to group the community in every village such that the community can be easily controlled and trained to enhance their skills. This group is known as KUBE. Batuyang is one of the villages which was effected by the Lombok earthquake in 2018. This condition causes an economic decline in the village. Approaches should be executed to improve the welfare of the community's economy through the KUBE program in Batuyang village. The efforts of the team to achieve these goals were identifying potentials, forming KUBE, and conducting counseling and training events. Based on the identification results, the team initiated a joint business group of Tobacco and Coffee. The counseling, training, and mentoring activities carried out by the team had a positive impact which is increasing the skills of the community, especially KUBE members, in processing, packaging, and marketing their products. As an outcome, they have a high selling value which is ultimately expected to improve their economy and welfare.